Application Of The Braden Scale Instrument in Detecting Risk of Decubitus - Armi Mawaddah; Afiatika Ahsani (International Journal of Health and Social Behavior, 2024)
Decubitus wounds are wounds caused by prolonged pressure on a prominent surface area of ​​the bone. Nurses play an important role in preventing the incidence of decubitus, especially by carrying out an early assessment of the risk of decubitus, namely by using the Braden Scale. Objective: to determine the risk of decubitus injuries using the Braden Scale. Method: This type of research is quantitative research with a descriptive research design. The sample in this study was 20 people using a non-probability accidental sampling. Inclusion criteria for this research were patients treated in hospital. Islam Malahayati Medan for more than 2 days of treatment, young elderly, middle elderly and old elderly patients. Data analysis in this study used SPSS 25 for Windows for descriptive statistics. Results: There were 7 people (35%) in the no risk category, 6 people (30%) in the mild risk category, 2 people (10%) in the moderate risk category and 4 people (20%) in the high risk category and 1 person (5%) severe risk category. Suggestion: Hospitals need to include the Braden Scale assessment format in the inpatient assessment format to detect the risk of decubitus injuries and carry out assessments on patients every day while the patient is hospitalized.